ChemInform Abstract: Highly Efficient Deoxygenation of Aryl Ketones to Arylalkanes Catalyzed by Dioxidomolybdenum Complexes. Issue 45 (October 2016) - Sousa, Sara C. A.; Fernandes, Tiago A.; Fernandes, Ana C.
Abstract: Catalyst is recyclable and reusable up to 12 times with only slight decrease in its activity.